Full versus partial collusion among brands and private label producers - Irina Hasnas; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
We analyze the incentives to collude when brand manufacturers compete with a private label producer of inferior quality. Full collusion is easier to sustain than partial collusion from the brands.perspective when horizontal differentiation is large and vertical differentiation is small. The private label firm is better off under full collusion than under partial collusion if goods are sufficiently homogenous (horizontal and/or vertical). Partial collusion could be preferred by the private label exactly when full collusion is easier to sustain. Improving the private label's quality makes full collusion more likely, either because it relaxes the brand producers' incentive constraint or because it shifts the preference of the private label firm from partial collusion to full collusion. Fully collusive behavior reveals itself through a nonnegative price effect on the brands' side caused by a quality increase of the private label good.
Keywords: L11; L13; 330; Oligopoly; Product Differentiation; Private Label; Collusion